Game sketching: Exploring approaches to research-creation for games. Issue 1 (1st April 2020) - Westecott, Emma
Digital games are a critical form in which makers express models of play that create meaning beyond entertainment. Game culture is pervasive and amidst a wider technological context that invites all our active participation provides one setting for creative self-expression. Games collapse the distance between makers and players in a uniquely active manner and whilst this paper centers on possibilities for game making, all players co-create their own gameplay experience, which holds potential for enacting individual agency. Based on experience introducing game design and development education at an art and design university over the past decade as part of the Digital Futures programme, this paper develops some early discussions around the concept of game sketching to both pedagogic and research-creation ends.